Chronic Ammonia Stress in Chinese Perch (Siniperca chuatsi): Oxidative Response, Nitrogen Metabolism, and Multi-Enzyme-Mediated Molecular Detoxification Defense Mechanisms - Yan Li; Ru Yang; Minghui He; Jianmei Su; Liwei Liu (Antioxidants)
Chinese perch (Siniperca chuatsi), an economically important freshwater fish in China, faces ammonia nitrogen stress under high-density aquaculture. This study investigated chronic ammonia nitrogen exposure effects on juvenile fish (95 ± 5 g) to establish safe concentration. Acute toxicity tests revealed a 96 h-LC50 of 12.91 mg/L ammonia nitrogen, with a safe concentration of 1.29 mg/L ammonia nitrogen (non-ionic ammonia: 0.097 mg/L). In 28-day chronic experiments with ammonia nitrogen levels at 0, 0.61, 1.29, and 2.58 mg/L, ammonia nitrogen induced hepatic oxidative stress, with total superoxide dismutase, catalase, and glutathione peroxidase activities and malondialdehyde content increasing proportionally to ammonia nitrogen concentration initially but declining over time. Concurrently, gill Na+-K+-ATPase activity was significantly suppressed, while the gene expression of ammonia transporters (rhag, rhbg, and rhcg) exhibited ammonia nitrogen concentration-dependent upregulation, inversely correlated with the exposure duration. Histological gill damage intensified at higher concentrations. Hepatic ammonia detoxification enzymes activities (asparagine synthase, glutamine synthetase, and glutamate dehydrogenase) and glutamine accumulation increased with ammonia nitrogen levels, aligning with gene expression trends, though enzyme activity diminished over time. Serum alanine aminotransferase and aspartate aminotransferase activities and their gene expressions rose with ammonia nitrogen levels, while total protein declined. These findings demonstrate that chronic ammonia nitrogen stress disrupts antioxidant capacity, osmoregulation, and nitrogen metabolism, compelling Chinese perch to mitigate toxicity via glutamine synthesis. To ensure sustainable aquaculture, ammonia nitrogen levels should remain below 1.29 mg/L under adequate dissolved oxygen conditions.